Perdebatan Teori Transisi Demokrasi - Alkatiri, Zeffry (Wacana, Journal of the Humanities of Indonesia, 2007)
This paper discusses the debate on the theories of democratic transition that has been going on since the 1960s. Democratic thoughts area always related to a context of change in a society. The theories of democratic transition had come to be debated again when the communist block countries and Russia changed their ideology and entered a democratic transition process. This debate provide a reference point and comparative framework that can be employed to evaluate socio-political changes in other countries that are experiencing similar democratic transition process and all of the consequences and challenges it poses.